PENGARUH MODEL PEMBELAJARAN KONVENSIONAL DAN ROLE PLAYING TERHADAP HASIL BELAJAR SISWA IPS MATA PELAJARAN EKONOMI DI SMAN 3 KOTA JAMBI - Imelda Devita; Mayasari Mayasari (SJEE (Scientific Journals of Economic Education), 2020)
This study aims to determine the comparison of the use of conventional learning models through the lecture model with the Role Playing learning model in economic subjects with the material of financial services institutions in class X IPS SMAN 3 Jambi City. The research design used a Quasi Experiment research method. The population in this study were 157 students from all class X IPS SMAN 3 Jambi City. Based on research results it can be explained that by using the learning model the objectives, competencies and student learning outcomes are expected to be achieved effectively and efficiently. Therefore, teachers are expected to be able to understand and be able to choose interesting and innovative learning models that will help students in the process of absorbing learning material.